Proton-induced X-ray emission (PIXE) analysis of trace elements of total atmospheric deposit (TAD) around a smelting industry: - Chigaekwu Godwin, EZEH; Paul Jerimiah, UGWO; Mayowa Festus, ADEBIYI; Emmanuel Olawale, ABIYE; Azuka Chinwe, ONWUDIEGWU; Ikechi Eusebius, OBIAJUNWA (Taylor & Francis Group, 2023)
An International Journal Of Taylor & Francis Group,P.16.